Processing pulse oximeter signals in exercise environment - Ho, Jolene Hui Ping (2014)
Pulse oximeter has become an important device to have to monitor the heart rate and oxygen saturation of the user. It is commonly used in hospitals and clinics but now it gradually starts to be used in home and exercise environments.